The Effect of Investment, Labor and Exports on Economic Growth in East Nusa Tenggara Province - Nono, Dedy Sergius; Tameno, Nikson; Tomasowa, Olivia L E. (Universitas Dharmawangsa Medan, 2025)
Economic growth is an important indicator in measuring the success of a region's development. Sustainable and inclusive economic growth is the main goal for every local government, including East Nusa Tenggara Province (NTT). There are several factors that influence economic growth, namely investment, labor and exports. Based on the discussion of the effect of investment, labor and exports on economic growth in East Nusa Tenggara Province, it can be seen that investment variables in the short and long term have no significant effect on economic growth in East Nusa Tenggara Province in 2003-2023, labor variables in the short and long term have a significant but negative effect on economic growth in East Nusa Tenggara Province in 2003-2023, export variables in the short and long term have no significant effect on economic growth in East Nusa Tenggara Province in 2003-2023, and simultaneously investment, labor and export variables in the short and long term have a significant effect on economic growth in East Nusa Tenggara Province in 2003-2023.